Organization of the Plasmid cpe Locus in Clostridium perfringens Type A Isolates - Miyamoto, Kazuaki (American Society for Microbiology, 2002)
Clostridium perfringens type A isolates causing food poisoning have a chromosomal enterotoxin gene (cpe), while C. perfringens type A isolates responsible for non-food-borne human gastrointestinal diseases carry a plasmid cpe gene. In the present study, the plasmid cpe locus of the type A non-food-borne-disease isolate F4969 was sequenced to design primers and probes for comparative PCR and Southern blot studies of the cpe locus in other type A isolates. Those analyses determined that the region upstream of the plasmid cpe gene is highly conserved among type A isolates carrying a cpe plasmid. The organization of the type A plasmid cpe locus was also found to be unique, as it contains IS1469 sequences located similarly to those in the chromosomal cpe locus but lacks the IS1470 sequences found upstream of IS1469 in the chromosomal cpe locus. Instead of those upstream IS1470 sequences, a partial open reading frame potentially encoding cytosine methylase (dcm) was identified upstream of IS1469 in the plasmid cpe locus of all type A isolates tested. Similar dcm sequences were also detected in several cpe-negative C. perfringens isolates carrying plasmids but not in type A isolates carrying a chromosomal cpe gene. Contrary to previous reports, sequences homologous to IS1470, rather than IS1151, were found downstream of the plasmid cpe gene in most type A isolates tested. Those IS1470-like sequences reside in about the same position but are oppositely oriented and defective relative to the IS1470 sequences found downstream of the chromosomal cpe gene. Collectively, these and previous results suggest that the cpe plasmid of many type A isolates originated from integration of a cpe-containing genetic element near the dcm sequences of a C. perfringens plasmid. The similarity of the plasmid cpe locus in many type A isolates is consistent with horizontal transfer of a common cpe plasmid among C. perfringens type A strains.